PERHITUNGAN PAJAK PENGHASILAN (PPh) PASAL 21 PEGAWAI TETAP MENGGUNAKAN TARIF EFEKTIF RATA-RATA (TER) - Chusnah, Shella Robbiul Chusnah; Sucahyati, Diarany (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2025)
This article discusses the calculation method for Income Tax Article 21 (PPh 21) using the Average Effective Rate (TER) approach, which has been established by the Directorate General of Taxes as part of efforts to simplify tax administration in Indonesia. The TER method is designed to facilitate tax deductions for permanent employees by calculating income tax based on a more efficient and standardized rate. The article explains the legal basis underlying the implementation of TER, its objectives in improving the tax deduction system, and the benefits for both employees and companies in terms of compliance and tax management. The technical process of calculating PPh 21 using the TER method is outlined in detail, covering steps from determining gross income to the correct deduction and reporting of taxes. The article also includes a practical case example that illustrates the application of TER in real-life situations, demonstrating how this method can enhance efficiency and reduce errors in tax calculations. While TER can improve tax administration efficiency, the article emphasizes the importance of a deep understanding of the applicable regulations and the need for caution in its application.